Targeting CD89 on tumor-associated macrophages overcomes resistance to immune checkpoint blockade. Issue 12 (2nd December 2022) - Xu, Lijun; Li, Bingyu; Pi, Chenyu; Zhu, Zhaohua; Tao, Fei; Xie, Kun; Feng, Yan; Xu, Xiaoqing; Yin, Yanxin; Gu, Hua; Fang, Jianmin
Abstract : Background: Despite the survival benefits observed with immune checkpoint blockade (ICB) treatment—programmed cell death-1/programmed cell death ligand-1 (PD-1/PD-L1), many patients with cancer have not benefited from these agents because of impaired antigen presentation and other resistance mechanisms. To overcome resistance to checkpoint therapy, we designed bispecific antibodies (BsAbs) targeting CD89 and tumor antigens. We demonstrated their immunomodulatory efficacy as a separate treatment strategy or combined with immune checkpoint inhibitors. Methods: We have previously generated a heterodimeric one-arm IgG1 Fc-based bispecific antibody. For animal efficacy studies, murine tumors in a humanized transgenic mice model were used to determine the effects of CD89-bispecific antibodies on antigen presentation and immune cell recruitment. The efficacy of the CD89 bispecific antibody against tumors resistant to pembrolizumab was evaluated in double-transgenic mice. Results: BsAbs targeting CD89 on tumor-associated macrophages (TAMs) increased the ratio of M1:M2 and activated the antigen presentation, leading to increased cytotoxic T cell-mediated tumor regression. CD89-BsAbs also potentiated a combinational antitumor effect with PD-1/PD-L1 inhibitors and overcame the ICB resistance by augmenting cytotoxic T-cell infiltration and reshaping tumor immune microenvironment. In an hCD89/hPD-1 double transgenic mouse model engrafted with pembrolizumab-resistant B16-HER2 tumor cells, the HER2-CD89 bispecific antibody potently inhibited tumor growth. Conclusions: CD89 BsAbs targeting tumor antigens and TAMs controlled tumor growth in animal models by improving antigen presentation and T-cell infiltration. Our results suggest a general strategy for overcoming resistance to ICB.